PENERAPAN MODEL PBL DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI MENELADANI ASMAUL HUSNA MENGGUNAKAN VIDEO PEMBELAJARAN DI SD NEGERI 050772 PANGKALAN SUSU - Muhammad Nasir (Journal of Community Devation, 2024)
This research aims to improve student learning outcomes on material emulating Asmaul Husna using learning videos at SD Negeri 050772 Pangkalan Susu, Langkat Regency, through the application of the Problem Based Learning (PBL) model. The PBL model was chosen because it can encourage students to think creatively and innovatively in solving problems related to the Asmaul Husna concept. This research was conducted in two cycles, where each cycle consisted of planning, implementation, observation and reflection. The results of data analysis show a significant increase in student learning outcomes, with an average value presentation before implementing the PBL model of 33.3%, increasing to 80% after implementation. Apart from that, student activity in learning has also increased, as can be seen from student participation during the learning process. The conclusion of this research shows that the Problem Based Learning (PBL) model is effective in improving student learning outcomes on material modeled after Asmaul Husna using learning videos. It is hoped that the results of this research can make a positive contribution to educators in designing more creative and relevant learning.